The Spanish Gypsy (Thomas Middleton, William Rowley, Thomas Dekker y John Ford, 1623) frente a La gitanilla (1613) de Cervantes: texto y contexto de una tragicomedia jacobea - Ruiz Notario, Sara (El Colegio de México, 2025)
By comparing La gitanilla and La fuerza de la sangre (Cervantes, Exemplary Novels, 1613) with the British tragicomedy The Spanish Gypsy (T. Middleton, W. Rowley, T. Dekker and J. Ford, 1623), this article hopes to demonstrate that certain differences between the British play and the Spanish plays on which it is based are the result of the acclimatization of stories written by Cervantes in the post-Tridentine Spain of Philip III, to the sociopolitical and ideological context of the British Protestant reign of James I. This is evident, for example, in the suppression of Leocadia’s pregnancy (La fuerza de la sangre) and the different image that is offered of the Gypsies (La gitanilla).